2001
DOI: 10.1186/1751-0147-42-287
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Melatonin Levels in Relation to the Light-Dark Cycle and Parental Background in Domestic Pigs

Abstract: Andersson H: Plasma melatonin levels in relation to the light-dark cycle and parental background in domestic pigs. Acta vet. scand. 2001, 42, 287-294. -To study porcine melatonin secretion in a stable environment 3 daytime (10.00 -15.00) and 3 nighttime (22.00 -03.00) plasma samples were collected by jugular venipuncture from 15 gilts, 16 sows, 3 boars and 48 piglets (24 females and 24 males from 8 litters) and analysed for melatonin content. Nighttime melatonin concentrations were higher than daytime melatoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…To the best of our knowledge, this study is the first one focused on evaluating biological profile and functional roles of SP MLT in livestock sires, particularly boars, used in commercial AI programs. The average SP MLT concentrations found in the present study were like those recently found by González-Arto et al (2016b) and close to those previously observed by Andersson (2001) in blood plasma samples collected from adult boars during daylight hours. The first noteworthy finding was the significant variability in the concentration of MLT among SP samples, which agrees with previous results achieved by González-Arto et al (2016b) in SP samples of different livestock males.…”
Section: Discussionsupporting
confidence: 93%
“…To the best of our knowledge, this study is the first one focused on evaluating biological profile and functional roles of SP MLT in livestock sires, particularly boars, used in commercial AI programs. The average SP MLT concentrations found in the present study were like those recently found by González-Arto et al (2016b) and close to those previously observed by Andersson (2001) in blood plasma samples collected from adult boars during daylight hours. The first noteworthy finding was the significant variability in the concentration of MLT among SP samples, which agrees with previous results achieved by González-Arto et al (2016b) in SP samples of different livestock males.…”
Section: Discussionsupporting
confidence: 93%
“…The effects of lighting conditions on endocrine hormones, and on melatonin are well‐known. Circulating levels of melatonin are higher at night compared to levels during the day, which is also applicable for pigs (Andersson, 2001). Oral administration of melatonin to rats for 9 weeks reduced insulin levels (Peschke, 2010; Ríos‐Lugo et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting lesions range from impaired horn production, with diffuse softening and discolouration in the horn of the sole [2] . The pathogenesis of "Rusterholz" ulcer is the circulatory disturbance in the corium due to primary damage and degeneration of the cells in the epidermis [3] . Localized contusion of the corium as a result of overloading and heel horn erosion is also considered to be a contributory factor in the development of sole ulcers in cattle.…”
Section: Introductionmentioning
confidence: 99%